Proposition of a Supporting Method for the Generation of Ergonomic Specifications - Gontijo L.A. (2015)
© 2015 The AuthorsThis research proposes the initial form of a method for industrial design development process. The main goal of this method is to help industrial design student to construct product design requirements considering ergonomic information. The proposed method focused on aspects involving interaction behavior process between human and product. Aspects like body movement, contact and abilities are considered inside the method. The method aims to investigate important information of the relationships between user and product, from two ways of comprehension and analysis. The first point of view considers the user and its way he manipulates and interacts with the product. And, the other is about what the product is demanding from human capabilities and what advantages are offered to the user. The proposal applied a pilot test to improve its possibilities of use and effectiveness comprehension by the students. The methodology applied used two questionnaires. The first questionnaire researches the way the student defines his criteria to select the information to build the requirements of conceptual product. The second questionnaire applied at the end of the process evaluates the scope of the method. In the middle of both questionnaires was exposed the methodology, was observed the product development process made by students, and applied the method. Final, analyzed the results of the method, and compared the results of the questionnaires, was identified some benefits on clearance the objective of the ergonomic information, needed to define the product conceptual requirements. The method provides detailed information allowing the student to identify ergonomic aspects that weren't considered in previous analyzes. These make corrections to the requirements of the project.